DEVELOPMENT OF A CARTESIAN COORDINATE MODULE TO THE INFLUENCE OF IMPLEMENTING THE ROUND CLUB LEARNING MODEL ON MATHEMATICS STUDENT LEARNING OUTCOMES - Gaurifa, Midarwati; Darmawan Harefa (Universitas Nias Raya, 2023)
The aim of the research is to determine the effect of the Round Club learning model on the cognitive learning outcomes of class VIII students at SMP Negeri 2 Telukdalam in the mathematics subject of number patterns for the 2022/2023 academic year. One solution to influence student learning outcomes, especially in number pattern material, is through the Round Club model where each group is taught to be responsible, give each other ideas about the material being discussed, and the interactions that are built are interactions that provide information and knowledge to each other. This research method is a quasi-experimental method which is quantitative in nature, namely in the experimental class the Round Club model is used, while in the control class the conventional method is used. The results of the research were that in the experimental class, by carrying out a pretest, the average learning outcome was 63.57 and the posttest obtained an average learning outcome of 83.21. Meanwhile, in the control class, the pretest obtained an average learning result of 57.93 and the posttest obtained an average learning result of 74.66 on the subject of the human digestive system for class VIII students at SMP Negeri 1 Telukdalam. The research conclusion based on hypothesis test calculations shows that tcount is 2.779, then the t price table is consulted with a significance level of 0.05 where ttable is 1.673. Because of the t table, Ha is accepted and Ho is rejected at the 5% significance level, which means